2010
DOI: 10.1292/jvms.10-0058
|View full text |Cite
|
Sign up to set email alerts
|

Current Levels of Heavy Metal Pollution in Africa

Abstract: ABSTRACT. Studies of environmental pollution in Africa indicate that toxic metal pollution has reached unprecedented levels over the past decade. Human exposure to toxic metals has become a major health risk on the continent and is the subject of increasing attention from national and international environmentalists. This paper reviews data from the past decade on environmental pollution in Africa and highlights countries where most heavy metal pollutions have been reported. Characteristics of heavy metal poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
81
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(81 citation statements)
references
References 45 publications
0
81
0
Order By: Relevance
“…In European rivers, Cd concentrations around 1 ppb or lower are typically reported (Pan et al, 2010), while higher values (up to 1 ppm) can occur in developing countries with rapidly growing industries (Yabe et al, 2010;Anetor, 2012). Cd is known to exert genotoxic and also carcinogenic activity (Waisberg et al, 2003;Bertin and Averbeck, 2006) and thus could possibly contribute to promotion of tumor formation in the aquatic organisms.…”
Section: Aop Case Study For Growth Impairment By Cadmiummentioning
confidence: 99%
“…In European rivers, Cd concentrations around 1 ppb or lower are typically reported (Pan et al, 2010), while higher values (up to 1 ppm) can occur in developing countries with rapidly growing industries (Yabe et al, 2010;Anetor, 2012). Cd is known to exert genotoxic and also carcinogenic activity (Waisberg et al, 2003;Bertin and Averbeck, 2006) and thus could possibly contribute to promotion of tumor formation in the aquatic organisms.…”
Section: Aop Case Study For Growth Impairment By Cadmiummentioning
confidence: 99%
“…Elevated heavy metal levels of Cd (0.345-0.18 mg kg −1 ) and Cr (24.11-2.4 mg kg −1 ) in lettuce and Zn (130.1-6.4 mg kg −1 ) in spinach were reported in Ethiopia from Akaki River which was polluted with untreated sewage and industrial effluents (Prabu 2009). An international study in Dandora municipal waste site, East of Nairobi, was conducted by the UN Environmental Programme (UNEP), and the study revealed high levels of pollution of heavy metals in soils such as Pb (264.0 mg kg −1 ), Hg (18.6 mg kg −1 ), Cd (40.0 mg kg −1 ), and other heavy metals (Cr, Mn, Fe, Cu, Zn, and Co) ( (UNEP) 2007, Yabe et al 2010. In Ghana, a related study was carried out at Kumasi dumpsites and high levels of Pb (54.6 mg kg −1 ), Cd (2.87 mg kg −1 ), Cu (1631.67 mg kg −1 ), and Zn (2606.0 mg kg −1 ) were reported in soils used for vegetable cultivation (Odai et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In most African countries, the reliance on pollution-prone technologies and inadequate controls on the discharge of pollutants from mining activities have worsened metal pollution [3]. Yabe et al [4] recently noted that contamination of the environment and food animals with toxic metals has reached unprecedented levels over the past decade and that human exposure to toxic metals has become a major health risk on the continent. This was tragically demonstrated by the recent Pb poisoning disaster in Nigeria, where more than 160 people died, mostly children under the age of five ( [5]; http://www.worstpolluted.org/files/FileUpload/files/2010/ WWPP-Report-2010-Top-Six-Toxic-Threats-Web.pdf).…”
Section: Introductionmentioning
confidence: 99%